Stress concentration analysis of short flat bars with projections under axial and shear loading using boundary element method - Liew, Yusheng. (2011)
Stress concentration increases due to the existence of stress raisers. Stress raisers can appear in the form of geometric discontinuities such as holes, notches and fillet, material irregularities due to fabrication or surface irregularities. Many instances of mechanical failure are attributed to the presence of stress raisers. In order to prevent catastrophic consequences, it is imperative to investigate the effects of such discontinuities. The boundary element method is employed to obtain the stress concentration factors of T-shaped filleted specimens under remote and local restraint conditions. The geometric parameters of these specimens were varied in order to determine the optimum configuration required to better design and prolong the lives of these components in operative machines. Computational results obtained from the analysis were compared and discussed with existing literatures that were reviewed. Results obtained indicated that the maximum meridional stress was found to be peaking in the middle section of the fillet. These results were found to be conclusive and in good agreement with other literature. It is recommended that increasing the radius of curvature of the fillet region or the ration of the fillet radius to shank depth, R/d, will result in a decrease in stress concentration factor.